A Study on the Role of Latest Technology in Sustainable Spiritual Tourism for Viksit Bharat - Anurag Singh; Sachin Malve; Sumona Ghosh (AG Volumes, 2026)
India, with its ancient spiritual heritage, is a global center for spiritual tourism. As the country strives towards its vision of Viksit Bharat 2047, it is essential to ensure that the spiritual tourism sector becomes both sustainable and technologically advanced. This paper explores how emerging technologies, such as Artificial Intelligence (AI), the Internet of Things (IoT), Virtual Reality (VR), Blockchain, and Big Data, can transform spiritual tourism into an environmentally responsible, culturally respectful, and economically inclusive industry. The paper also highlights successful use cases and offers policy recommendations for integrating technology into the spiritual tourism ecosystem to support sustainable development. Through a literature review, case studies, and analysis of recent data, the paper demonstrates how technological advancements can enhance tourist satisfaction, optimize resource use, and empower local communities.